2022
DOI: 10.29390/cjrt-2021-068
|View full text |Cite
|
Sign up to set email alerts
|

Development and internal validation of an equation using anthropometric measures to predict correct endotracheal tube insertion depth

Abstract: Purpose: To develop, internally validate, and assess the utility of implementing a regression model for determining endotracheal tube (ETT) insertion depth. Research methods: We recorded height, weight, age, sex, ETT internal diameter (ID), lip marking, and tracheal position from the electronic record from a random subset of 2,000 intubated subjects obtained from 1 January 2009 to 5 May 2012. A multivariable linear regression model was constructed and validated by a nonparametric bootstrapping technique using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…3 In a recently published study, Volsko et al proposed a height-based formula using advanced statistical methods based on a retrospective review of chest radiographs in children on mechanical ventilator support. 5 They found that it facilitated correct ETT placement after internally validating that in a small cohort of patients. However, accessibility and radiation are the main drawbacks of using X-rays and CT scans.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…3 In a recently published study, Volsko et al proposed a height-based formula using advanced statistical methods based on a retrospective review of chest radiographs in children on mechanical ventilator support. 5 They found that it facilitated correct ETT placement after internally validating that in a small cohort of patients. However, accessibility and radiation are the main drawbacks of using X-rays and CT scans.…”
Section: Discussionmentioning
confidence: 91%
“…Only a few studies have validated the formula for depth of insertion of ETT in children. [1][2][3][4][5] Among them, only two studies are available for the Asian ethnic population. 1,4 Both these studies were conducted in Korea.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation